The development and structure of industry in the district of Bağcılar, Istanbul - Temurçin Kadir (Bulletin of Geography. Socio-Economic Series)
As a part of Istanbul Metropolis, Bağcılar has been one of the leading centers of developments in parallel with the developments in outward-oriented economy and industrialization in the 1980’s in Turkey. After these years of experiencing rapid urbanisation and industrialisation, the district has taken a look far from its earlier appearance. During this period of migration fact from suburbs to the cities, one of those who took the biggest share is Bağcılar. The purpose of this study is to determine the historical development of industrialization in Bağcılar and the causes of this development, its structure, and its sectors distribution. As an operation of a regional industry, this study handles the features of Bağcılar District Location, the factors that affect the industry in the District, the sectors distribution of industry and environmental issues.